The Effectiveness of the Problem-Based Learning Model in Enhancing Critical Thinking Skills: A Gender-Differentiated Analysis in Biology Learning - Nunung Nurhayati; Tri Wahyu Agustina; Ucu Julita (Indonesian Technology and Education Journal, 2026)
This study examined the effectiveness of the Problem-Based Learning (PBL) model in improving students’ critical thinking skills in Biology and investigated whether gender influenced critical thinking performance on the Human Circulatory System topic. A quasi-experimental pretest–posttest control group design was employed. The participants were 72 eleventh-grade students from a Madrasah Aliyah Negeri in Cianjur, West Java, Indonesia. They were divided into an experimental group taught through PBL (n = 36) and a control group receiving conventional instruction (n = 36). Data were collected using a ten-item essay test covering five indicators of critical thinking and analyzed using Two-Way Analysis of Variance. The results showed that the learning model significantly affected students’ critical thinking skills (F = 33.845, p < 0.001), with the PBL group achieving higher scores than the conventional group. Gender also had a significant effect (F = 11.049, p = 0.001), as female students obtained higher mean scores than male students. However, the interaction between learning model and gender was not significant (F = 1.143, p = 0.288), indicating that the effectiveness of PBL was relatively consistent across gender groups. The study was limited to one school, one Biology topic, and existing classroom groupings, which restricted random assignment and may have introduced selection bias. Nevertheless, the findings support PBL as an effective instructional approach for strengthening critical thinking in Biology education. This study extends previous research by jointly examining instructional model and gender, while showing that gender differences in performance do not significantly moderate the effectiveness of PBL.